Mapping adolescent literacy across L1 backgrounds: Linguistic and discourse features as predictors of persuasive essay quality. (February 2022) - Jo, Claire W.
Abstract: Proficiency in academic writing in secondary school is often a contributor to success in adulthood in both academic and professional spheres. Yet, despite extensive English-as-a—Foreign-Language (EFL) research at the college level, academic writing in EFL adolescent learners is considerably understudied, especially in the domain of discourse components. This study examined academic writing (AW) features that predict writing quality in 220 persuasive essays written by adolescents from three different first language (L1) backgrounds: EFL students from China and Russia, and native English-speaking students from the US. Essays were coded for linguistic (lexical and syntactic) and discourse features, and scored for writing quality. Regression analyses revealed that several AW features (i.e., lexical diversity, syntactic complexity, diversity of discourse markers, and the presence of a conclusion) significantly predicted writing quality demystifying criteria for effective essay writing in secondary school. Other discourse features (i.e., types of supporting examples) were not related to differences in writing quality, but their frequencies varied by L1. Findings shed light on the AW features relevant to the design of EFL writing instruction and assessment tools, and document different trends in the discourse features that are more frequently used to support arguments in writing across L1 groups. Highlights: Several linguistic and discourse features in essays predict writing quality. Types of supporting examples are not related to differences in writing quality. Types of supporting examples document some different discourse patterns by L1. Findings shed light on teachers' underlying expectations of effective academic writing. Findings may inform the design of EFL writing instruction and assessment tools.